PENERAPAN PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 1 LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Putria Tanjung, Selvia; Febriana, Rina; Lovia, Lita (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was carried out due yo the studentsâ low learning achievement in mathematics in class XI IPA SMAN 1 Luhak Nan Duo. This research was aimed at revealing whether the mathematics conceptual understanding of the studentsâtaught by using Everyone Is A Teacher active learning was better than that of studentsâ taught by using conventional learning. This was an experimental research which used random toward the subject design. Based on the result of data analysis it was found that the two sample classes were normally distributed and homogenous. Furthermore, the result of t-test indicated that the value of Â was higher than Â in which Î± was 0.05. this result showed that the mathematics conceptual understanding of the studentsâ taught by using Everyone Is A Teacher active learning was better than of studentsâ taught by using conventional learning in class XI IPA SMAN 1 Luhak Nan Duo registered in academic year 2013/2014.